PERANCANGAN APLIKASI TATA KELOLA DOKUMEN BERBASIS WEB - Ardhia Fasha Bening Safhabil; Made Kamisutara (Simtek : jurnal sistem informasi dan teknik komputer, 2026)
Document management in companies that is still carried out manually or has not been integrated into a centralized system may lead to various problems, including difficulties in document retrieval, the risk of archive loss, data duplication, and inconsistencies in document versions. These conditions can hinder the effectiveness and efficiency of company operations. This study aims to design a web-based document governance application that supports systematic and structured processes of document storage, management, retrieval, and control. The system development method employed in this research is Rapid Application Development (RAD), which emphasizes a fast and adaptive design process through iterative stages of requirements planning,system design, and evaluation with active user involvement. The results of thisstudy produce a proposed design of a web-based document governanceapplication equipped with role-based user access control. The proposed systemdesign is expected to serve as a solution to improve the effectiveness, efficiency,and security of corporate document management.